One of each - Hoberman, Mary Ann.; Priceman, Marjorie (Boston : Little, Brown, 1997)
Oliver Tolliver, who lives alone in his little house with just one of everything, discovers that it is more fun to have two of everything and share with a friend.
Keywords: Sharing -- Fiction; Friendship -- Fiction; Dogs -- Fiction; Cats -- Fiction; Stories in rhyme